PENERAPAN METODE PEMBELAJARAN HYBRID LEARNING PADA ERA NEW NORMAL - Tri Rahmawati; Ines Heidiani Ikasari (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2023)
The teaching and learning process is a process that involves participants and educators which is successful when there is interaction between the two parties. Along with the development of information technology, especially the internet in the information system. In this new normal era, the most feasible hybrid model is to implement a rotation system. The purpose of this research is to find out the level of efficiency in the use of hybrid learning methods for SMK students which helps the student learning process to be better and also to overcome the problems faced by teachers and students in the learning process taking place during the new normal period, so that it can find out the obstacles in accessing material as well as assignments using a computer/laptop or mobile device connected to the internet network.